THE FACTORS THAT INFLUENCE E-BANKING SERVICE QUALITY IN GUINEA’S COMMERCIAL BANKS - Kaba Traore; Ooi Kok Loang (International Journal of Accounting, Finance and Business, 2023)
This research aims to identify the Factors That Influence E-Banking Service Quality In Guinea's Commercial Banks. To find out the strong influence of e-banking on customer's trust, loyalty and satisfaction. Also, it is to study the significant difference between EBSQ and its independent variable: efficiency, Reliability, security and privacy, and Responsiveness. The questionnaire survey will be used for data collection and analysis for this research. It will be conducted using descriptive statistics using SPSS version 27. Moreover, the research questionnaire will be based on Guinea customers' experience. Thus, a total of 188 questionnaires were distributed to the respondents. The target respondents will be bank customers with experience in using e-banking of Guinea commercial banks. Rapid changes in technology have improved the advancement of financial institutions. Generally, it provides electronic service to its customers. Using e-Banking to increase customer satisfaction and give banks a competitive edge is fast becoming one of the essential financial services. The banking industry can focus on what satisfies customers most by understanding the relative importance of service quality dimensions.